Autism – Neurodiversity and Subjectivity - Ziemna, Joanna (Sensus Historiae, 2020)
The article touches upon the issue of the identity of neurodiverse people, with emphasis on autism. The problem is connected with the way of viewing the autistic - the way in which they are de-personified by the neurotypical society. They are driven away from what in the antropocentric world is understood as being “human” and “subject” towards the category of “non-people”: either as unemotional robots or aliens in human body, or as unintelligent bodies devoid of agency and in need to be taken care of, like pets. Their otherness is emphasised by being different from neurotypicals’ mode of cognition and embeddedness in language. The author puts a special emphasis on how neurodiversity exposes us to multiple kinds of subjectivity, amongst which neurotypicality is but one of many others.